THE IMPACT OF COMPANY FINANCIAL PERFORMANCE ON ECONOMIC GROWTH - Putra, Aji Binawan; Musthofa, Muhammad Wakhid (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: The relationship between companies and economic growth needs to be analyzed. What if the company's performance is not effective then economic growth will not be in good condition or the company's financial performance does not affect economic growth. Methods: This research is a quantitative study using the balanced scorecard method with variables namely financial ratio indicators ROA and DER, and economic growth as measured by Gross Domestic Product (GDP). Data were collected from the financial reports of 11 companies for 10 years, and were processed using panel data regression analysis with the Random Effect Model (REM) approach with the help of the Econometric Views 10 Application (Eviews 10). Results: The results of the study show that ROA and DER have no effect on Indonesia's economic growth. Conclusion and suggestion: This study can be used as an additional reference in financial management activities, and then for institutions that have supervisory authority to ensure that the profits and debts of a company must be strictly controlled so that in the future financial performance can increase economic growth.